2020
DOI: 10.2147/opth.s275968
|View full text |Cite
|
Sign up to set email alerts
|

<p>Five-Year Patterns of Diabetic Retinopathy Progression in US Clinical Practice</p>

Abstract: Purpose To characterize the natural course of diabetic retinopathy (DR) in contemporary clinical practice. Patients and Methods This was a retrospective analysis of US claims data collected between January 1, 2006, and April 30, 2017. Patients aged ≥18 years with continuous medical and prescription insurance coverage for 18 months before DR diagnosis (index date) and for a follow-up period of 5 years were included (N=14,490). The time and risk of progressing to severe n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
2
23
2
Order By: Relevance
“…Data from a retrospective analysis that used medical claims data for patients with DR who had not received anti-VEGF therapy, laser photocoagulation, intravitreal steroid treatment or retinal surgery during the baseline period support the interpretation of our data for the native mild-to-moderate NPDR subgroup. The authors of this analysis reported that the risk of DR progression and DME over 5 years was highest among patients with an initial diagnosis of moderate and severe NPDR, respectively, and that patients with mild NPDR were the least likely to progress 8. A separate post hoc analysis of data from the OLE after RIDE/RISE showed that patients who required a higher number of PRN ranibizumab injections tended to have a longer duration of DME and greater retinal thickening than those who required fewer injections; they also received more focal macular laser surgery, which was indicative of chronic disease 9…”
Section: Discussionmentioning
confidence: 98%
“…Data from a retrospective analysis that used medical claims data for patients with DR who had not received anti-VEGF therapy, laser photocoagulation, intravitreal steroid treatment or retinal surgery during the baseline period support the interpretation of our data for the native mild-to-moderate NPDR subgroup. The authors of this analysis reported that the risk of DR progression and DME over 5 years was highest among patients with an initial diagnosis of moderate and severe NPDR, respectively, and that patients with mild NPDR were the least likely to progress 8. A separate post hoc analysis of data from the OLE after RIDE/RISE showed that patients who required a higher number of PRN ranibizumab injections tended to have a longer duration of DME and greater retinal thickening than those who required fewer injections; they also received more focal macular laser surgery, which was indicative of chronic disease 9…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, increased macular vessel area was extracted from the UWFA frames of moderate and severe NPDR eyes compared to PDR eyes [23]. Another study demonstrated a higher risk of DME development in moderate and severe NPDR compared to PDR [24]. Further studies investigating the integrative impact of DR severity compared or combined with quantitative angiographic features on future treatment should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…If a prophylactic regimen were adopted across the United States, the pool of diabetic patients who now qualify for injection therapy would increase substantially, further compounding costs. 19 Policy makers who are setting reimbursement levels for various procedures should be aware of the possibility of financial incentives for two treatment strategies that are equally efficacious for patient care, but one of which costs the healthcare system significantly more. 7 Further reductions in vitrectomy reimbursements, which have already been falling over time, may paradoxically increase overall costs to the healthcare system by driving more practices toward an aflibercept-based strategy for treating diabetic vitreous hemorrhage.…”
Section: A Caveat About Anti-vegf Injectionsmentioning
confidence: 99%